TRANSPARANSI PENGELOLAAN KEUANGAN DI BADAN KESATUAN BANGSA POLITIK DAN PERLINDUNGAN MASYARAKAT KABUPATEN KEPULAUAN TALAUD - LALOMBOMBUIDA, YOKLIN; LENGKONG, FLORENCE; LONDA, VERY (Sam Ratulangi University, 2018)
Abstract: Board Unity Nation Politik and Protection of Talaud Islands Regency in the management of regionalfinance is needed transparency (transparency) to the community. Local governments in their duties andfunctions must ruun a good government, especially in terms of financial management. Through transparency,local financial management can be done effectively and efficiently, both administratively and also from theavailability and accessibility of documents, clarity and completeness of imformation, process openness, andregulatory framework. As transparency is one form of government accountability to the community, efforts toimfrove the management of financial management is also one of the fundamental aspects for the realization ofgood governance for the community is openness, involvement and ease of access for the community to theprocess of governance. The purpose of this research is to know the transparency of regional financialmanagement in Badan Unity Nation politics and Protection of Talaud Islands regency community. Thisresearch is a descriptive research with qualitative approach.Data analysis techniques used were observation,interview, documentation.Based on the research results obtained can be seen that the lack of informationdisclosure in financial management that causes weakness of financial management transparency.Therefore itis expected that the government this cease National Unity Board of politics and profection of the communitymore open in accounting for regional finances for the administration of government can run well.Keywords: Transparency of Regional Financial Management